Feedback control strategy for state‐of‐charge balancing and power sharing between distributed battery energy storage units in DC microgrid. Issue 6 (18th January 2023) - Ding, Xiao; Wang, Wen; Zhou, Meina; Yue, Yufei; Chen, Qinze; Zhang, Chaofeng; Tang, Xin; Li, Jianqi
Abstract: Different line resistances between battery energy storage systems (BESSs) and the bus cause the problem of state‐of‐charge (SOC) unbalance between the batteries. SOC unbalance brings about battery over‐charge or over‐discharge, which reduces the battery life. This paper proposes an SOC feedback control strategy to achieve both output power sharing and SOC equalization between the BESSs. The average SOC of the batteries is set as the reference of each SOC control loop, and the control objectives are achieved by regulating the output voltage of the energy storage converters. The state space model of the proposed control method is established for stability analysis and control parameter design. The parameters are then designed in detail according to the dynamic and steady‐state performance. Simulation and experiment verified that the proposed control strategy can achieve accurate SOC equalization and output power sharing when the line resistances and the battery capacities are different. Abstract : State‐of‐charge (SOC) balancing and power sharing with unbalanced line resistances in the DC microgrid are achieved by the proposed SOC balancing method. It helps extend the lifetime of the battery in the battery energy storage system and maintain the stability of the DC microgrid.